The effects of drafting on stroking variations during swimming in elite male triathletes - Chollet, D.; Hue, O.; Auclair, F.; Millet, G.; Chatard, J. C. (European Journal of Applied Physiology, 2000)
The aim of this study was to determine the effects of drafting behind another swimmer on the metabolic response and stroke characteristics. Six highly trained male triathletes performed two maximal 400-m swims, one in a drafting (D) and one in a non-drafting condition (ND). Their metabolic response was assessed by measuring the oxygen uptake (V˙O2) and the blood lactate concentration at the end of each 400 m. Swimming velocity, stroke frequency, stroke length, and stroke index (velocity multiplied by stroke length) were recorded every 50 m. In the D and ND conditions, there was no difference in V˙O2 [66.7 (1.7) ml · kg-1 · min-1 vs 65.6 (1.2) ml · kg-1 · min-1, respectively], however, the lactate concentrations were lower in D than in ND [9.6 (0.9) mM vs 10.8 (0.9) mM, respectively, P < 0.01]. In D, the performance [1.39 (0.02) m · s-1 vs 1.34 (0.02) m · s-1, respectively, P < 0.01] and the stroking parameters (i.e., stroke length and stroke index) increased significantly, while the stroke frequency remain unchanged. In D, a stable pace was maintained, while in ND, velocity decreased significantly throughout the 400 m. In D, the performance gains were related to the 400-m D velocity (r=0.78, P < 0.05), and to the body fat mass (BFM, r=0.99, P < 0.01). The stroke index in D was also related to BFM (r=0.78, P < 0.05). Faster and leaner swimmers achieved greater performance gains and stroke index when drafting. Thus, drafting during swimming increases the performance and contributes to the maintenance of stable stroking parameters such as stroke frequency and stroke length during a 400-m swim.